(untitled) (Ricos Biology, 2023)
A novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV- 2) causes COVID-19; a newly emerged global pandemic disease and found to be more infective and more pathogenic than former human respiratory corona viruses due to its higher specific receptor binding affinity. Exposed COVID-19 data clearly recognize that the human immune response to SARS-CoV-2 is the prime factor affecting the course of disease. This article places emphasis on virus pathogenesis, host cell interaction, immunological response for COVID-19 trying to light on the obscured areas of this novel human health menace.